Uzun kemik yerleşimli osteoid osteomada görüntüleme yardımlı minimal invaziv cerrahi - (:unkn) unknown (My University, 2006)
Amaç: Bu prospektif çalışmada, görüntüleme yardımlı minimal invaziv cerrahinin uzun kemik yerleşimli osteoid osteoma tedavisindeki etkinliği değerlendirildi. Çalışma planı: Uzun kemik yerleşimli osteoid osteoma nedeniyle 14 hastaya (11 erkek, 3 kız; ort. yaş 13; dağılım 4-22) görüntüleme yardımlı minimal invaziv lezyoniçi genişletilmiş küretaj uygulandı. Ameliyat öncesinde tüm hastalar konvansiyonel radyografi, bilgisayarlı tomografi (BT), tüm vücut kemik sintigrafisi ve manyetik rezonans görüntüleme (MRG) ile değerlendirildi. Nidusun anatomik yerleşimi, ince-kesit BT (1-1.5 mm) veya MRG üzerinde yapılan ölçümlerle belirlendi ve nidus, görüntüleme yardımlı minimal invaziv teknikle tam olarak çıkarıldı. Hastalar ağrı şiddeti açısından ameliyat öncesi ve sonrasında görsel analog skala veya yüz ağrı skalası ile değerlendirildi. Ameliyat sonrasında hastalar ortalama 17 ay (dağılım13-31 ay) takip edildi. Sonuçlar: Görsel analog skala skorunun ameliyat öncesi ortalama değeri 7.9±1.2 (oldukça şiddetli ağrı) iken, ameliyat sonrasında bu değer 0.3±0.6 (ağrı yok) olarak belirlendi (p<0.05)

Objectives: In this prospective study, we evaluated the efficiency of image-guided minimal invasive surgical resection of osteoid osteomas of the long bones. Methods: Fourteen patients (11 males, 3 females; mean age 13 years; range 4 to 22 years) with osteoid osteoma of the long bones underwent image-guided minimal invasive intralesional extended curettage. Preoperatively, all the patients were evaluated by plain radiographs, computed tomography (CT), bone scintigraphy, and magnetic resonance imaging (MRI). Localization of the nidus was determined by measurements on thin-section (1-1.5 mm) CT scans and MR images and complete excision of the nidus was performed by image-guided minimal invasive technique. All the patients were evaluated by visual analog scale or faces pain scale to determine pain levels before and after surgery. The mean follow-up period was 17 months (range 13 to 31 months). Results: The mean visual analog scale scores were 7.9±1.2 (severe pain) and 0.3±0.6 (no pain) before and after surgery, respectively (p<0.05). Bone grafting or internal fixation were not required during operations. No perioperative or postoperative complications or recurrences were encountered. Early mobilization was possible in all the patients. At the final follow-ups, all the patients were asymptomatic and had full functional use of their operated extremities. Conclusion: Image-guided minimal invasive surgery is effective in the local control of osteoid osteomas affecting the long bones and causes less morbidity. This technique also provides a good identification of the nidus intraoperatively.
Image-guided minimal invasive surgical resection of osteoid osteomas of the long bones
Keywords: Ortopedi; Radyoloji, Nükleer Tıp, Tıbbi Görüntüleme; Cerrahi